2015
DOI: 10.1111/tct.12269
|View full text |Cite|
|
Sign up to set email alerts
|

Learning opportunities in ‘student assistantships’

Abstract: The assistantship fulfils its aims for many students, but individual experience gained varies considerably. Some opportunities are not being taken, with 'patient-oriented' opportunities more likely to be missed, whereas others are not available during placements. Supervisors may overestimate the educational value of the assistantship, with implications for its management and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Nevertheless, like previous work, our study has demonstrated the variability in student experiences on assistantship placements. 9 23–25 Unlike other studies, 24 the majority of participants in our study reported students having the opportunity to complete tasks independently under appropriate supervision, suggesting that these assistantships provide a realistic preparation for the demands of being an F1. However, the accounts of consultants being unwilling for students to undertake routine tasks undertaken by an F1 doctor suggest a need to address a lack of awareness of the assistantships' aims among senior clinicians.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, like previous work, our study has demonstrated the variability in student experiences on assistantship placements. 9 23–25 Unlike other studies, 24 the majority of participants in our study reported students having the opportunity to complete tasks independently under appropriate supervision, suggesting that these assistantships provide a realistic preparation for the demands of being an F1. However, the accounts of consultants being unwilling for students to undertake routine tasks undertaken by an F1 doctor suggest a need to address a lack of awareness of the assistantships' aims among senior clinicians.…”
Section: Discussionmentioning
confidence: 64%
“…There is also a lack of qualitative exploration of supervisors' views of student assistantships, which has been shown to contradict those of students. 23 Finally, despite highlighting some elements of assistantships that improve preparedness, the findings may not be transferable to all assistantships as assistantship models are variable and poorly defined in both of these studies. Although current qualitative studies have explored assistantship alignment with students' first F1 post, their results do not thoroughly contrast the differences between the experiences of students who undertook placements aligned to their F1 post and those who did not.…”
Section: Introductionmentioning
confidence: 72%
“…When considering these results it is also important to consider that in order to provide situated learning opportunities through increased participation, an assistantship period requires each individual student to be engaged and partaking in the F1-related tasks. Previous assistantship research has shown that this is not guaranteed; as students do not always utilise every learning opportunity presented to them (Burford et al, 2015). However, the emphasis of the SA was on the 'readiness' of the placement to support greater participation of students in the work of the practice setting (Reid et al, 2014).…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…However, individual perceptions of preparedness are no guarantee of actual practice performance (Monrouxe et al, 2014) and, as argued by Kilminster et al (2011), the focus on individual skills and knowledge, rather than the individual in the context of the 'placement environment' is of concern. The latter point is taken up by both Reid et al (2014) and Burford et al (2015) who independently investigated how learning opportunities were likely to be affected by the placement learning environment and the learning culture of the multi-disciplinary team.…”
Section: Introductionmentioning
confidence: 99%
“…We have published papers reporting on the use of student assistantships to ease the transition into practice in 2012 and in April 2015 . In this issue are two further articles.…”
mentioning
confidence: 99%